Critical assessment of the proposed Monti II regulation – more courage and strength needed to remedy the social imbalances - Bruun, Niklas; Bücker, Andreas (Brussels, 2012)
"This Policy Brief presents The Proposal for the Council Regulation submitted by the Commission in March 2012 (also known as the Monti II proposal) and conducts a critical assessment of whether it can contribute to reconciling economic freedoms and social rights. Although it provides an opportunity for the European Union institutions to show that Social Europe is not dead the authors argue that the proposal needs substantial rewriting recognising the autonomy of social partners and a margin of manoeuvre for trade union action. If the EU Institutions wish to reestablish legitimacy for the European project, Monti II must be significantly improved, by clearly stating that its purpose is to change the restrictive practice regarding strikes established by the judgments in Viking and Laval as far as it is possible within the framework of the Lisbon Treaty."